Perennial grassland agriculture restores critical ecosystem functions in the U.S. Upper Midwest - Wepking, Carl; Mackin, Hunter C.; Raff, Zach; Shrestha, Debendra; Orfanou, Anna; Booth, Eric G.; Kucharik, Christopher J.; Gratton, Claudio; Jackson, Randall D. (Frontiers in Sustainable Food Systems, 2022)
Dominant forms of agricultural production in the U.S. Upper Midwest are undermining human health and well-being. Restoring critical ecosystem functions to agriculture is key to stabilizing climate, reducing flooding, cleaning water, and enhancing biodiversity. We used simulation models to compare ecosystem functions (food-energy production, nutrient retention, and water infiltration) provided by vegetation associated with continuous corn, corn-soybean rotation, and perennial grassland producing feed for dairy livestock. Compared to continuous corn, most ecosystem functions dramatically improved in the perennial grassland system (nitrate leaching reduced 90%, phosphorus loss reduced 88%, drainage increased 25%, evapotranspiration reduced 29%), which will translate to improved ecosystem services. Our results emphasize the need to incentivize multiple ecosystem services when managing agricultural landscapes.